2013
DOI: 10.1088/0967-3334/34/3/307
|View full text |Cite
|
Sign up to set email alerts
|

Compression-induced hyperaemia in the rabbit masseter muscle: a model to investigate vascular mechano-sensitivity of skeletal muscle

Abstract: In conclusion, for its high sensitivity and reliability this technique is adequate to characterize mechano-vascular reactivity and may prove useful in the investigation of the underlying mechanisms, with implications in the control of vascular tone and blood pressure in health and disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…The lack of this local regulatory mechanism in isolated vessel preparations likely explains why, when multiple compressive stimuli are delivered to isolated feed arteries, a potentiation of the dilatation is observed ( Clifford et al, 2006 ) rather than an attenuation, as reported in the present and other studies in humans and intact animals ( Tschakovsky et al, 1996 ; Turturici and Roatta, 2013a ; Messere et al, 2017a , b ).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…The lack of this local regulatory mechanism in isolated vessel preparations likely explains why, when multiple compressive stimuli are delivered to isolated feed arteries, a potentiation of the dilatation is observed ( Clifford et al, 2006 ) rather than an attenuation, as reported in the present and other studies in humans and intact animals ( Tschakovsky et al, 1996 ; Turturici and Roatta, 2013a ; Messere et al, 2017a , b ).…”
Section: Discussionsupporting
confidence: 65%
“…The hyperemic response to MC was previously shown to exhibit a progressive attenuation in response to repetitive stimulation. This was first observed in the masseter muscle of the anesthetized rabbit ( Turturici and Roatta, 2013a , b ) and was later confirmed in the human forearm ( Messere et al, 2017b ). The effect was initially attributed to the possible inactivation of the putative mechano-sensitive vascular structures ( Turturici and Roatta, 2013b ; Messere et al, 2017b ) according to similar inactivation patterns described for vascular mechano-sensitive structures ( Honore et al, 2006 ; Earley and Brayden, 2015 ).…”
Section: Introductionmentioning
confidence: 70%
“…muscle blood flow; hyperemia; muscle compression; tissue oxygenation SINCE THE SEMINAL WORK of Mohrman and Sparks (39) several studies have demonstrated that a rapid and transient hyperemic response can be elicited by a short-lasting muscle compression (10, 30, 38, 56 -60). Although the underlying mechanisms have not been fully identified, this phenomenon has been well documented in different experimental models, such as the isolated muscle (39), awake and anesthetized animals (57,58,60), and humans (10,30,38,56). In addition, a rapid dilatory response to compressive stimuli has also been observed in isolated feed arteries (7).…”
mentioning
confidence: 97%
“…Vascular reactivity to mechanical compression takes the form of a rapid dilatation and results in a prompt and short lasting hyperemia. This phenomenon has been originally observed in the isolated muscle (Mohrman and Sparks 1974) and has also been documented in isolated feed arteries (Clifford et al 2006), in intact animals (Turturici et al 2012;Turturici and Roatta 2013a) and in humans, in both upper (Kirby et al 2007;Messere et al 2017b) and lower limbs (Credeur et al 2015;Messere et al 2017a). This mechano sensitivity of the muscle vasculature is likely to contribute also to the hyperemia that develops with passive movements (Wray et al 2005) as well as with muscle contraction (Kirby et al 2007;Messere et al 2017a) and is considered to have a role in the hyperemia at the beginning of exercise (Clifford 2007).…”
Section: Introductionmentioning
confidence: 68%